К проблеме рециклинга СО2 в зонах субдукции - Перчук А.Л.; Корепанова О.С. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Московский государственный университет им. М. В. Ломоносова», 2011)
The disbalance between the amount of CO2 subducted and emitted from arc volcanism and that the subducted and emitted CO2 in subdcution zones arise a problem of the release and evolution of the rest of the CO2. Experimental modeling of the oceanic crust-mantle interaction was carried out for two systems blueschist-olivine and blueschist-silicate marble-olivine at the conditions of high pressure and heterogeneous temperature representative to the oceanic crust-mantle wedge transition in the Cascadia subduction zone. The experiments demonstrate possibility of the intensive CO2 degassing in the forearc area which is controlled by solution of calcite in hydrous fluid followed by magnesite deposition in the overriding mantle rocks. It is suggested that magnesite-forming process is able to retain carbone dioxide in the mantle and transport it by viscous mantle flow from the forarc mantle to the greater depth till the thermodynamic stability field of magnesite. Experimental modeling also reveals development of the ultrahigh pressure metasomatic column consisting of 4 zones: Fe-MgCa-carbonate | dolomite | diopside | magnesite.
Keywords: СУБДУКЦИЯ; SUBDUCTION; ДИОКСИД УГЛЕРОДА; CARBON DIOXIDE; ДЕГИДРАТАЦИЯ; DEHYDRATION; МЕТАМОРФИЗМ; METAMORPHISM; ЭКСПЕРИМЕНТ; EXPERIMENT; КАРБОНАТЫ; CARBONATES; 552.13:552.16:550.4.02